Gamma knife radiosurgery in patients with persistent acromegaly or Cushing's disease: long‐term risk of hypopituitarism. (5th October 2015) - Cohen‐Inbar, Or; Ramesh, Arjun; Xu, Zhiyuan; Vance, Mary Lee; Schlesinger, David; Sheehan, Jason P.
Summary: Introduction: For patient with a recurrent or residual acromegaly or Cushing's disease (CD) after resection, gamma knife radiosurgery (GKRS) is often used. Hypopituitarism is the most common adverse effect after GKRS treatment. The paucity of studies with long‐term follow‐up has hampered understanding of the latent risks of hypopituitarism in patients with acromegaly or CD. We report the long‐term risks of hypopituitarism for patients treated with GKRS for acromegaly or CD. Methods: From a prospectively created, IRB‐approved database, we identified all patients with acromegaly or CD treated with GKRS at the University of Virginia from 1989 to 2008. Only patients with a minimum endocrine follow‐up of 60 months were included. The median follow‐up is 159·5 months (60·1–278). Thorough radiological and endocrine assessments were performed immediately before GKRS and at regular follow‐up intervals. New onset of hypopituitarism was defined as pituitary hormone deficits after GKRS requiring corresponding hormone replacement. Results: Sixty patients with either acromegaly or CD were included. Median tumour volume at time of GKRS was 1·3 cm 3 (0·3–13·4), and median margin dose was 25 Gy (6–30). GKRS‐induced new pituitary deficiency occurred in 58·3% ( n = 35) of patients. Growth hormone deficiency was most common (28·3%, n = 17). The actuarial overall rates of hypopituitarism at 3, 5 and 10 years were 10%, 21·7% and 53·3%, respectively. The median time to hypopituitarism was 61 months after GKRS (range, 12–160). Cavernous sinus invasion of the tumour was found to correlate with the occurrence of a new or progressive hypopituitarism after GKRS ( P = 0·018). Conclusions: Delayed hypopituitarism increases as a function of time after radiosurgery. Hormone axes appear to vary in terms of radiosensitivity. Patients with adenoma in the cavernous sinus are more prone to develop loss of pituitary function after GKRS.